2020
DOI: 10.3847/1538-4357/ababab
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Reconnection and Hot Spot Formation in Black Hole Accretion Disks

Abstract: Hot spots, or plasmoids, forming due to magnetic reconnection in current sheets, are conjectured to power frequent X-ray and near-infrared flares from Sgr A * , the black hole in the center of our Galaxy. It is unclear how, where, and when current sheets form in black-hole accretion disks. We perform axisymmetric general-relativistic resistive magnetohydrodynamics simulations to model reconnection and plasmoid formation in a range of accretion flows. Current sheets and plasmoids are ubiquitous features which f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(168 citation statements)
references
References 86 publications
14
152
2
Order By: Relevance
“…The highest-energy particles resulting from reconnection are further energized by shear-driven acceleration, i.e., reconnection can mediate particle injection into shear acceleration. Our work lends support to spinesheath models of jet emission and can explain the origin of radioemitting electrons at the boundaries of relativistic jets (see Ripperda et al 2020 for an alternative explanation).…”
Section: Discussionsupporting
confidence: 75%
“…The highest-energy particles resulting from reconnection are further energized by shear-driven acceleration, i.e., reconnection can mediate particle injection into shear acceleration. Our work lends support to spinesheath models of jet emission and can explain the origin of radioemitting electrons at the boundaries of relativistic jets (see Ripperda et al 2020 for an alternative explanation).…”
Section: Discussionsupporting
confidence: 75%
“…An important assumption made in our model is that we include only thermal electron populations. For sources such as Sgr A*, emission from electrons with a non-thermal energy-distribution function is thought to be important to explain the observed time variability and the high frequency emission (Ball et al 2016;Mao et al 2017;Gravity Collaboration et al 2018;Davelaar et al 2018;Ripperda et al 2020;Dexter et al 2020;Porth et al 2020;Petersen and Gammie 2020). However, at 230 GHz, time-averaged images of this model will look similar to the thermal case when adding nonthermal electrons (Davelaar et al 2018), although it is shown in that work that high-spin models of M87 do become more optically thin because of this addition.…”
Section: Radiative Modelsmentioning
confidence: 99%
“…In SANE simulations, on the other hand, no magnetic 'pile-up' occurs, causing a radical change in the observed source morphology. Whether an accretion flow is MAD or SANE depends on the initial conditions of the magnetic field and the size of the accretion disc (see, e.g., Ripperda et al (2020). The radiative models considered in this work consist of a single-electron-temperature, disc-dominated model (Mościbrodzka et al 2009), and a two-electron-temperature, jet-dominated model (Mościbrodzka et al 2014;Davelaar et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The longest variability timescales in the observed TeV emission, for example, in M87, have recently been linked to recurring periods of efficient Blandford/Znajek (Blandford & Znajek 1977) type outflows induced by the accretion of magnetic flux tubes (Parfrey et al 2015;Mahlmann et al 2020). Reconnection and plasmoid formation in BH accretion processes are likely to act on much shorter timescales (studied in the ideal limit by, e.g., Nathanail et al 2020) and involve relevant physical nonideal electric fields (analyzed in the resistive limit by, e.g., Ripperda et al 2020). A large array of work makes use of numerical laboratories set up in (GR)FFE in order to simulate the most extreme environments of the universe while constantly breaking their own limits.…”
Section: Introductionmentioning
confidence: 99%